Positive Associations of Dietary Marine Omega-3 Polyunsaturated Fatty Acids with Lung Function: A Meta-analysis (P18-087-19). (13th June 2019) - Patchen, Bonnie; Xu, Jiayi; Barr, R Graham; Eekelen, Ester van; Dupuis, Josee; North, Kari; Gharib, Sina; Lahousse, Lies; Lemaitre, Rozenn; Manichaikul, Ani; Mutsert, Renee de; Houston, Denise; et al.
Abstract: Objectives: Our previous study found positive associations between plasma levels of the omega-3 polyunsaturated fatty acids (n-3 PUFAs), specifically docosahexaenoic acid (DHA) and docosapentaenoic acid (DPA), and lung function, especially in current smokers. Given that plasma n-3 PUFA concentrations are driven by dietary intake, we extended our prior findings to a larger sample by studying dietary n-3 PUFAs, including DHA, DPA, eicosapentanoic acid (EPA), and alpha-linolenic acid (ALA), and fish intake. Methods: Nine cohorts from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium ( N  = 37, 077 black and white participants) contributed dietary intake and lung function data. In each cohort and each ancestry, separately, associations of dietary n-3 PUFA/fish intake with lung function were estimated in linear regression models. Models were extended to test for n-3 PUFA/fish × smoking status interaction. Fixed-effects meta-analysis was used to generate summarized effect estimates across the cohorts and ancestries. Results: Dietary DPA, DHA, EPA, and fish intake were positively associated with forced expiratory volume in one second (FEV1 ) and forced vital capacity (FVC). ALA had little to no association with these lung function parameters. Associations were similar for black and white participants, and consistent in direction and magnitude across most cohorts. For all participants, 1 standard deviation (SD) higher intake of DPA (∼30 mg/d), DHA (∼200 mg/d), and EPA (∼150 mg/d) were associated with 12–16 mL higher FEV1 and 10–15 mL higher FVC. The effect estimates for fish were in the same direction but smaller in magnitude. Smoking modified the associations of DHA and EPA with FEV1 and FVC; 1 SD higher intake of DHA and EPA were associated with 28–32 mL higher FEV1 and 24–25 mL higher FVC in current smokers, 17–21 mL higher FEV1 and 7–12 mL higher FVC in former smokers, and little to no association in never smokers. Conclusions: Dietary DHA, DPA, and EPA, but not ALA, are positively associated with FEV1 and FVC, corroborating our previous findings for plasma n-3 PUFAs. This large cross-sectional meta-analysis shows that diets rich in marine n-3 PUFAs are associated with higher lung function, especially for current and former smokers. Funding Sources: National Institutes of Health, NHLBI and NIDDK.